Governance of flood disaster framework: a way forward managing flood in Malaysian context - Maidin, Siti Sarah; Othman, Marini; Ahmad, Mohammad Nazir (Elsevier, 2018)
Specific to flood management, poor governance reflects weakness in tracking and monitoring of flood activities and systems, poor mitigation of flood risk, and non-optimal use of given (as well as invested) resources. This study proposes a framework to govern flood disaster management in Malaysia. The Control Objective for Information and Related Technologies, Hyogo Framework for Action and Sendai Framework for Disaster Risk Reduction principles were used as guiding principles for the development of the proposed framework. A qualitative field study was deployed for the identification of baseline practices in governing the floods in Malaysia. As a result, a Governance for Flood Disaster framework which consists of ten (10) building block components, was constructed. The framework capitalizes on the strength of elements found from the existing practices documented in the National Security Council’s Directive and the Kemaman Standard Operating Procedure, whilst filling up the gaps by adopting the principles and spirit from COBIT, Hyogo and Sendai frameworks. It is hoped that further studies can be undertaken to develop and establish each of the components within the framework and that the framework itself can be further tested and improved over time.